Filkovi na kalhoty: Příspěvek k teorii písňového textu (1984) - Pistorius, Vladimír (Lidé města, 2020)
Filkovi na kalhoty (loosely translated: “For Filek’s Trousers”, meaning something along the lines of “A Somewhat Meaningless Study”) was significant samizdat from in the 1980s. It was dedicated to analysing the verses (i.e. versology) of the lyrics of popular folk songs at the time. The author shows that we perceive both music and the song lyrics/poem rhythmically, whereby it is possible to differentiate the outer linguistic, or acoustic, rhythm of the work, and the inner rhythm, characterised by its subjective perception. In this sense, the author analyses various types of poetic rhythms, and he concludes that Czech poems and song lyrics usually use different principles of rhythmics. Songs can depend on affecting emotions using non-textual means, but they are also bound by the formal rules of strophes, length, etc. Thus, only a very small number of song lyrics can stand alone as independent literary works (poems), and that in both the formal and perceptive context.